A complete narrative review on polypharmacy: role of clinical pharmacist in managing interventions in polypharmacy and improving patient outcomes - Diya Agarwal; Koushika Reddy; Gayathri Prasanna; Fanindra Sanke; G. Tulja Rani; Swathi Nalla (International Journal of Basic & Clinical Pharmacology, 2026)
Polypharmacy, commonly defined as the concurrent use of multiple medications, has emerged as a significant global health concern, especially among elderly patients with multimorbidity. It is associated with an increased risk of adverse drug reactions, drug–drug interactions, prolonged hospital stays, and poor medication adherence, ultimately leading to unfavorable clinical outcomes. This review critically evaluates existing literature on polypharmacy, focusing on its etiology, associated risks, and clinical consequences. It examines patient-, physician-, and healthcare system-related factors contributing to inappropriate prescribing. Additionally, the role of clinical pharmacists and the application of assessment tools such as Beers criteria, STOPP/START criteria, and the medication appropriateness index are analyzed. The findings highlight that inappropriate polypharmacy is driven by multiple factors, including fragmented healthcare delivery, lack of medication review, and limited awareness among healthcare providers. Clinical pharmacists play a pivotal role in mitigating these risks by identifying potentially inappropriate medications, conducting medication reviews, and implementing deprescribing strategies. The use of standardized tools and multidisciplinary collaboration has been shown to improve medication appropriateness and patient safety. Polypharmacy remains a complex challenge requiring a coordinated and systematic approach. Integration of clinical pharmacy services into routine healthcare practice significantly enhances medication safety and clinical outcomes. Clinical pharmacists are essential in promoting rational pharmacotherapy and reducing medication-related harm through targeted interventions and patient-centred care.